Electro-Catalytic Biodiesel Production from Canola Oil in Methanolic and Ethanolic Solutions with Low-Cost Stainless Steel and Hybrid Ion-Exchange Resin Grafted Electrodes - Allioux, Francois-Marie; Holland, Brendan J.; Kong, Lingxue; Dumée, Ludovic F. (Frontiers in Materials, 2017)
Biodiesel is a growing alternative to petroleum fuels and is produced by the catalysed transesterification of fats in presence of an alcohol base. Transesterification processes using homogeneous catalysts are considered to be amongst the most efficient methods but rely on the feedstock quality and low water content in order to avoid undesirable saponification reactions. In this work, the electro-catalytic conversion of canola oil to biodiesel in a 1% aqueous methanolic and ethanolic reaction mixture was performed without the addition of external catalyst or co-solvent. An inexpensive stainless steel electrode and a hybrid stainless steel electrode coated with an ion-exchange resin catalyst were used as cathode materials while the anode was composed of a plain carbon paper. The cell voltages were varied from 10 to 40 V and the reaction temperature maintained at 20 or 40°C. The canola oil conversion rates were found to be superior at 40°C without saponification reactions for cell voltages below 30 V. The conversion rates were as high as 87% for the hybrid electrode and 81% for the plain stainless steel electrode. This work could inspire new process development for the conversion of high water content feedstock for the production of second-generation biodiesel.